Guía práctica para informar un melanoma cutáneo - Ortiz González, Ana; Sánchez Espinosa, Alberto; Pérez Parra, David; Capozzi Cárdenas, Claudia Alejandra; Ortiz Reina, Sebastián (Archivos de Patologia, 2024)
Sin resumen